Productivity measurement - Awuah, Frank (My University, 2011)
One of the most important industries in the world today is software development. It has become an essential part of an organisation’s production and management processes. Software development projects are growing larger in size and becoming more complicated and at the same time faster turnaround times are required. Therefore software development teams are expected to be highly productive. Hence measurement of productivity of software development projects has become an aspect of high interest to management. The purpose of the research was to explore the perceptions of and measurements of productivity of software development projects. This included exploring the levels of awareness and understanding of productivity measurement of software development projects among professionals and the practical ways in which productivity is measured. A qualitative research methodology was followed in order to adequately capture the richness of perceptions and levels of understanding, frustrations, challenges and the depth and breadth of the topic. Depth interviews were the instrument used to gather the data. The interview reports were then analysed using content analysis and cognitive mapping. The findings were further discussed with a control group which is made up of a panel of senior experts in the field. There is a high level of productivity awareness among software development professionals. Professionals are conscious about productivity and its continued improvements. However, only a few of the respondents understand and appreciate the contribution that the knowledge and the right application of productivity rate of a development team, for example, has on the success of the project. Among the respondents who understand and appreciate the need of using a productivity rate for accurate project planning and management, function point analysis was the most supported. The proponents of lines of code productivity measurement admit that it is not a perfect measure but simple to use. iii Productivity measurement and the correct application of the outcomes aid in proper project planning, ensures that there is better conformance to project schedule, helps with monitoring and control and intelligent outsourcing, aids in eliciting top management support and ultimately, leading to improved project delivery and project success.
MBA - WBS
Keywords: Software development; Productivity; Project management